Elemental composition of natural populations of key microbial groups in Atlantic waters. (13th May 2013) - Grob, Carolina; Ostrowski, Martin; Holland, Ross J.; Heldal, Mikal; Norland, Svein; Erichsen, Egil S.; Blindauer, Claudia; Martin, Adrian P.; Zubkov, Mikhail V.; Scanlan, David J.
Summary: Intracellular carbon (C), nitrogen (N) and phosphorus (P) content of marine phytoplankton and bacterioplankton can vary according to cell requirements or physiological acclimation to growth under nutrient limited conditions. Although such variation in macronutrient content is well known for cultured organisms, there is a dearth of data from natural populations that reside under a range of environmental conditions. Here, we compare C, N and P content of Synechococcus, Prochlorococcus, low nucleic acid (LNA) content bacterioplankton and small plastidic protists inhabiting surface waters of the North and South subtropical gyres and the Equatorial Region of the Atlantic Ocean. While intracellular C:N ratios ranged between 3.5 and 6, i.e. below the Redfield ratio of 6.6, all the C:P and N:P ratios were up to 10 times higher than the corresponding Redfield ratio of 106 and 16, respectively, reaching and in some cases exceeding maximum values reported in the literature. Similar C:P or N:P ratios in areas with different concentrations of inorganic phosphorus suggests that this is not just a response to the prevailing environmental conditions but an indication of the extremely low P content of these oceanic microbes.